PENINGKATAN SERVICE BAWAH MELALUI PERMAINAN MODEL LETABOL (LEMPAR TANGKAP BOLA) PADA HASIL BELAJAR BOLA VOLI - Muhdhor, Muhdhor (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
This study aims to find out how much the increase in bottom service ability through the letabol model (throwing catch the ball) on the learning outcomes of Class V students at SD Negeri Tlogosari Wetan 02 Pedurungan District for the 2018/2019 school year.This study uses the Class Action Research (CAR) method with a research design of cycle I and cycle II to increase the ability to serve down through the letabol model (throwing and catch the ball) on the learning outcomes of Class V students in the second semester of SD Negeri Tlogosari Wetan 02 Pedurungan DistrictThe results showed the results in the first cycle with bottom service activities through traditional games 17.85% with the success of students'. The average success percentage increased to 89.28% 33 students who scored above the minimum completeness criteria (KKM) from 39 students with significant changes. Conclusions: 1) there is an increase in the bottom serve through the game of cat and mouse on the learning outcomes of 39 students who get above the minimum completeness criteria of 75 that have been set. 2) traditional games are very effective in providing stimulus to students to improve student learning outcomes. In the 2013 curriculum, which prioritizes the assessment of real processes and results, traditional games are very helpful in improving the ability to serve under volleyball.